The determinants of voluntary carbon offsetting: A micro-econometric analysis of individuals from Germany and the United States - Andreas Ziegler; Claudia Schwirplies (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper examines the determinants of voluntary individual carbon offsetting, i.e. the financial compensation of emissions from energy use. In contrast to former studies in this field, we particularly consider a comprehensive set of factors that are discussed in the context of voluntary contributions to public goods, such as psychological motives or social norms. The empirical analysis is based on unique data from representative surveys among more than 2000 citizens from Germany and the United States. These data reveal a higher extent of the past purchase of carbon offsets in the United States. In both countries, our micro-econometric analysis with discrete choice models indicates a strong positive correlation between the perceived contribution of this offsetting mechanism to climate protection and both actual carbon offsetting in the past and the planned purchase of carbon offsets in the future. In Germany, psychological motives such as the feeling of warm glow play an additional important role, while in the Unites States social motives such as expectations from the society are of a high relevance. Interestingly, a high environmental preference (measured by the membership in an environmental organization and the identification with green politics) is significantly correlated with already purchased carbon offsets in the United States, but not in Germany. These results suggest that not only the whole society in Germany has a lower average acceptance of carbon offsetting, but also that environmentally conscious people in this country obviously did not consider carbon offsetting as a measure to avoid further anthropogenic global warming so far.
Keywords: Q54; Q58; H41; 330